Taking a stand: The embodied, enacted and emplaced work of relational critique. (November 2019) - Bell, Emma; de Gama, Nadia
We reflect here on our experience as critical scholars in an academic organization when confronted with an expectation that we remain value-neutral about a political act which we, and many others, found reprehensible. Our experience relates to the Academy of Management response to the travel ban implemented by President Trump in January 2017 which denied US entry to citizens from seven Muslim majority countries. By exploring how the concept of 'taking a stand' was used by the Academy of Management leadership to try to silence politics, and the response that this generated within the critical management studies community, we draw attention to the impossibility of separating management scholarship from questions of ethics and politics. We highlight the gendered nature of struggles to be critical in uncritical spaces and draw attention to the importance of embodied, enacted and emplaced work as the basis for developing relational practices of critique.